2019
DOI: 10.1107/s2056989019010764
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Hirshfeld surface analysis of a new dithioglycoluril: 1,4-bis(4-methoxyphenyl)-3a-methyltetrahydroimidazo[4,5-d]imidazole-2,5(1H,3H)-dithione

Abstract: In the title dithioglycoluril derivative, C19H20N4O3S2, there is a difference in the torsion angles between the thioimidazole moiety and the methoxyphenyl groups on either side of the molecule [C—N—Car—Car = 116.9 (2) and −86.1 (3)°, respectively]. The N—C—N bond angle on one side of the dithioglycoluril moiety is slightly smaller compared to that on the opposite side, [110.9 (2)° cf. 112.0 (2)°], probably as a result of the steric effect of the methyl group. In the crystal, N—H...S hydrogen bonds link adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The versatility of acyl thioureas stems from their ease of preparation and ability to introduce different functionalities, resulting in compounds with very interesting biological properties including antifungal (del Campo et al, 2002Campo et al, , 2004, antitumor Herna ´ndez et al, 2005), antiviral, antibacterial, herbicidal, insecticidal and pharmacological activities (Binzet et al, 2006;Saeed et al, 2010). Recently, our research group reported the synthesis and crystal structures of a number of thiourea derivatives (Asegbeloyin et al, 2018(Asegbeloyin et al, , 2019Okpareke et al, 2020;Oyeka et al, 2021). In a continuation of our series on thiourea derivatives, we present herein the crystal structure, Hirshfeld surface and computational study of a new potential biologically active thiourea derivative with an aminoanthraquinone moiety.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The versatility of acyl thioureas stems from their ease of preparation and ability to introduce different functionalities, resulting in compounds with very interesting biological properties including antifungal (del Campo et al, 2002Campo et al, , 2004, antitumor Herna ´ndez et al, 2005), antiviral, antibacterial, herbicidal, insecticidal and pharmacological activities (Binzet et al, 2006;Saeed et al, 2010). Recently, our research group reported the synthesis and crystal structures of a number of thiourea derivatives (Asegbeloyin et al, 2018(Asegbeloyin et al, , 2019Okpareke et al, 2020;Oyeka et al, 2021). In a continuation of our series on thiourea derivatives, we present herein the crystal structure, Hirshfeld surface and computational study of a new potential biologically active thiourea derivative with an aminoanthraquinone moiety.…”
Section: Chemical Contextmentioning
confidence: 99%